2019
DOI: 10.3390/nu11102435
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seeds Proanthocyanidins: An Overview of In Vivo Bioactivity in Animal Models

Abstract: Over the last decade, proanthocyanidins (PACs) are attracting attention not only from the food industry but also from public health organizations due to their health benefits. It is well-known that grapes are a good source of PACs and for that reason, the industry is also focused on grape by-products identification and bioactivity evaluation. Grape seeds extract (GSPE) is a rich source of PACs, mainly composed of monomeric catechin and epicatechin, gallic acid and polymeric and oligomeric proanthocyanidins. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 84 publications
3
82
0
1
Order By: Relevance
“…However, the polymerization of the molecules is known to affect their bioavailability, so further research is needed to clarify the potential of tannins as a dietary supplement for humans. [ 51 ]. Tannins are rarely present in the oil obtained from Vitis sp.…”
Section: Grapes Seeds and Seed Extracts: Natural Sources Of Nutrmentioning
confidence: 99%
“…However, the polymerization of the molecules is known to affect their bioavailability, so further research is needed to clarify the potential of tannins as a dietary supplement for humans. [ 51 ]. Tannins are rarely present in the oil obtained from Vitis sp.…”
Section: Grapes Seeds and Seed Extracts: Natural Sources Of Nutrmentioning
confidence: 99%
“…GSSE is a complex polyphenol mixture exerting a wide range of beneficial effects against obesity, dyslipidemia, hypertension, inflammation, neuronal injury, and lipotoxicity [ 141 , 142 ]. Most of these metabolic improvements seem to be attributed to its antioxidant and free radical-scavenging properties [ 143 , 144 ]. Charradi and colleagues [ 145 ] have shown that compared to chow-fed Wistar rats, those exposed to a HFD for 6 weeks doubled the weight gain and induced brain lipotoxicity as indicated by elevated levels of malondialdehyde and carbonylated proteins, and lower levels of antioxidant markers including glutathione peroxidase and SOD.…”
Section: Role Of Antioxidants/anti-inflammatory Agents In the Cnsmentioning
confidence: 99%
“…This effect is probably related to the high content of proanthocyanidins in GM, mainly composed of catechin, gallic acid and anthocyanin glucosides (Nudda et al, ). Proanthocyanidins in in vitro and in vivo studies have demonstrated to possess relevant antioxidant and anti‐inflammatory effects (Bashir, Manoharan, & Miltonprabu, ; Pinna, Morazzoni, & Sala, ; Rodríguez‐Pérez, García‐Villanova, Guerra‐Hernández, & Verardo, ).…”
Section: Discussionmentioning
confidence: 99%